Terrorism, Drug Trafficking, and the Globalization of Supply - Joel Hernández (Perspectives on Terrorism)
This case study analyzes the diversification of both terrorist groups and drug traffickers and the convergence between the two types of organizations in recent decades. As financial markets have become globalized, so have opportunities for illicit groups to transact with each other. The article builds on the collapse of Lebanese Canadian Bank in 2011 after its designation by the U.S. Treasury Department as a money-laundering financial institution tied to global drug trafficking and to Hezbollah. It follows the trajectory of two Hezbollah-associated drug kingpins: Ayman Joumaa, who facilitated trade between Hezbollah and the Zetas, and Maroun Saade, who was apprehended attempting to connect Hezbollah to the Taliban. In its analysis of the histories, motivations, and relationships among these three groups, the article reflects on relationships currently in existence between terrorist and drug-trafficking organizations, and on the implications of the possible directions these relationships might take in the future.